Answer:
The answer is x=−1247
Step-by-step explanation:
Let's solve your equation step-by-step.
1+39(12−44)=x
Step 1: Simplify both sides of the equation.
1+39(12−44)=x
1+−1248=x
(1+−1248)=x(Combine Like Terms)
−1247=x
−1247=x
Step 2: Flip the equation.
Answer: x=−1247
D) is the answer i already done that question
Answer:
rate of change = -32 feet/second
Step-by-step explanation:
h(t) = 64 – 16t2
t = time (seconds)
Look at the start of time where t = 0
h(t) = 64 - 16 * (0) * 2 = 64 feet
Then look at the specified time where t = 1.25 seconds
h(t) = 64 - 16 * (1.25sec) * 2 = 24 feet
rate of change = rate of change y / rate of change x
x = time, y = height
rate of change = (24 - 64) / (1.25 - 0) = -32 feet/second
Answer:
15
Step-by-step explanation:
a^2 + b^2 = c^2
20^2 +b^2 = 25^2
400 + b^2 = 625
-400 -400
b^2 = 225
b = √225
b = 15
The answer should be:
20.875
Hope this helps.